PENGARUH KETEGASAN SANKSI, PENGETAHUAN, TAX AMNESTY, KUALITAS PELAYANAN FISKUS, KESADARAN, PENERAPAN E-SPT, TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI: Dibuat Oleh Suci Fitriyani, Muhamad Yusuf, Yohani (Dosen dan Mahasiswa FEB Universitas Muhammadiyah Pekajangan Pekalongan) - muhamad yusuf; Suci Fitriyani; Yohani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
This study aims to examine the effect of several independent variables such as the firmness of tax sanctions, tax knowledge, tax amnesty, the quality of tax authorities, taxpayer awareness, the application of e-spt to the dependent variable, namely the compliance of individual taxpayers in the KPP Pratama Batang. The sample used in this study were 100 respondents with calculated using the Slovin formula. The method of determining the sample used in this study is the accidental sampling method (accidental sampling by taking cases or respondents who happen to be available or available somewhere in the context of the study), while the data processing method used is multiple linear regression analysis using the program SPSS 16.0. The results of this study indicate that 1) The firmness of tax sanctions does not significantly influence the compliance of individual taxpayers with a significance value of 0.840 > 0.05. 2) Tax knowledge has no significant effect on individual taxpayer compliance with a significance value of 0.746 > 0.05. 3) Tax Amnesty has a significant effect on the compliance of individual taxpayers with a significance value of 0.018 < 0.05. 4) The quality of fiscal services significantly influences the compliance of individual taxpayers with a significance value of 0.048 < 0.05. 5) Awareness of taxpayers has a significant effect on compliance of individual taxpayers with a significance value of 0.041 < 0.05. 6) The application of E-SPT does not significantly influence the compliance of individual taxpayers with a significance value of 0.882 > 0.05. Keywords: firmness of tax sanctions, tax knowledge, Tax Amnesty, quality of tax authorities, awareness of taxpayers, application of E-SPT, compliance of taxpayers.